The Concept of Arabic Language Learning Programs in Madrasah Tsanawiyah Pekanbaru - Mutia; Hakmi Wahyudi; Izzatul Mellati; Nuraini; Fadhlilul Ilmi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This article aims to examine the concept of Arabic language learning programs in Madrasah Tsanawiyah Pekanbaru, particularly in relation to the understanding and objectives of learning. The method used is descriptive qualitative through teacher interviews and classroom observation. The results of the study show that teachers understand the learning program as an integrated system covering planning, implementation, and evaluation to develop students' communicative competence. Learning is implemented communicatively with the integration of vocabulary, grammar, and conversation. The program objectives are formulated based on the four language skills with an emphasis on the active use of Arabic. Implementation is supported by activities such as Arabic Day and Hiwar Club. The main obstacles include low student motivation and limited media and facilities. In general, the program is in line with the Merdeka Curriculum but requires strengthening of strategies and the learning environment.